1999
DOI: 10.1002/(sici)1522-2675(19990908)82:9<1311::aid-hlca1311>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3′-Sugar- and Base-Modified Nucleotides and Their Application as Potent Chain Terminators in DNA Sequencing

Abstract: Two 3′‐modified and three base‐modified ddNTPs were synthesized and tested with several DNA polymerases for incorporation activity. Starting from 3′‐azido‐3′‐deoxythymidine (AZT; 1), we were able to produce 3′‐deoxy‐3′‐isocyanato‐thymidine and 3′‐deoxy‐3′‐isothiocyanatothymidine (3 and 4, resp.) in a rapid synthesis based on the solid‐support approach (Scheme 1). These 3′‐functionalities could be used to attach a spacer molecule via urea and thiourea groups, respectively. Since the thus‐obtained tethered nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…90 By choosing this position, modifications can easily be introduced into the uridine or cytidine precursors.…”
Section: Figure 15supporting
confidence: 87%
See 1 more Smart Citation
“…90 By choosing this position, modifications can easily be introduced into the uridine or cytidine precursors.…”
Section: Figure 15supporting
confidence: 87%
“…Although the exocyclic amino functions were assumed to be important for Watson-Crick base pairing it has been shown that cytidine terminators labeled at the exocyclic NH 2 -group act as substrates for DNA-polymerases with perfect termination quality. 90 By choosing this position, modifications can easily be introduced into the uridine or cytidine precursors.…”
Section: Figure 15mentioning
confidence: 99%
“…Similar results were obtained with a 2Ј,3Ј-dideoxyadenosine 5Ј-triphosphate 6-N-labelled with JA242 and CY5 14 via a propyl linker as a shorter spacer (data not shown). Together with the 4-N-dye-labelled dideoxycytidine 5Ј-triphosphates 9 we were able to show that the modification of the exocyclic amino groups does not decrease the acceptance of the nucleotides as potent chain terminators in DNA sequencing.…”
Section: -N-ja242-modified Nucleotide 7 As Terminator In Dnasequencin...mentioning
confidence: 90%
“…Recently, our group has succeeded in showing that 4-N-dyelabelled 2Ј,3Ј-dideoxycytidine 5Ј-triphosphates serve as efficient terminators in DNA sequencing. 9 These promising results led us to develop a similar synthesis for purine nucleotides. In this paper we describe the synthesis of 2Ј,3Ј-dideoxyadenosine 5Ј-triphosphate bearing a longer chain amino linker at the exocyclic 6-N-position and labelled at the aliphatic amino group with the fluorescent dye JA242.…”
mentioning
confidence: 99%
“…Στις παραπάνω δύο εργασίες αναφέρεται αποµόνωση του προϊόντος σε εξαιρετική απόδοση (>95%) µε µοναδικό µειονέκτηµα τον σχετικά µεγάλο χρόνο αντίδρασης (36 h). Ως υπόστρωµα έχει χρησιµοποιηθεί142 και η προστατευµένη διδεοξυ-ουριδίνη και η αντίδραση γίνεται παρουσία 2χλωροφαινυλο-διχλωροφωσφορικού εστέρα σε πυριδίνη, ωστόσο δεν αναφέρεται αποµόνωση του παραγώγου αλλά χρήση του ως έχει στη συνέχεια της συνθετικής πορείας. Ίσως αξίζει να αναφερθεί ότι οι παραπάνω συνθήκες χρησιµοποιήθηκαν132 και για την µετατροπή του C4 καρβονυλίου σε C4 αµινοµάδα σε µια σειρά 4-αζιδο-ουριδινών οι οποίες µετατράπηκαν σε 4αζιδο-κυτοσίνες, στα πλαίσια ανάπτυξης αντι-ιϊκών φαρµάκων.…”
unclassified